Intergeneration relationship, psychology and social support among elderly care: A case study in Kota Kinabalu, Sabah - Nurul Hudani Md Nawi; Habibie Ibrahim; Puteri Hayati Megat Ahmad (2020)
This research is intended to describe the views of adults (caregivers) on inter generational relationships, psychological support and social support in the care of the elderly. Therefore, qualitative data is used in detail to achieve that objective. A total of six adult caregivers participated in this study. The study participants consisted of men and women who had relationships with the elderly whether as children, adopted children, grandchildren or other extended family members who considered themselves as a family and lived in the vicinity of Kota Kinabalu. Data were analyzed using thematic analysis by Braun and Clarke (2006). The results of the study seem to indicate that the value of the society’s respect for parents is still held by children as young people. As a result of this respect for parents comes a sense of responsibility and affection among the older children to take care of their parents and this shows good inter generational relationships. The findings also show that adult caregivers need social and psychological support in the process of caring for their parents. This study has implications for senior citizen policy by highlighting the need to formulate a holistic module based on the National Citizenship Policy (DWEN). It needs an improvement in the country’s action plan to ensure the module more integrated related to well-being and quality of life for caregivers and the elderly.